Experiences with welfare, rehabilitation and reintegration of prisoners: Lessons learned? - Charlotte Gisler; Ineke Pruin; Ueli Hostettler (United Nations Research Institute for Social Development (UNRISD), 2018)
Globally, at least 11 million people are held in prisons and other penal institutions, a number which has increased by more than 10 percent over the past decade. Prisoners often come from marginalized groups in society with limited economic opportunities, and children in prison are mostly those without adequate care and support systems. The number of elderly people in penal institutions is also increasing in many countries with ageing populations and increased poverty among the elderly. Without adequate public policies that can provide social services and support to inmates and their families, correctional services risk perpetuating cycles of criminal behaviour and exacerbating poverty and inequality. Designing and implementing comprehensive policies based on internationally agreed norms and standards is essential in today's era of sustainable development that pledges to leave no one behind - offering a chance for inmates and the released to be full members of society.
Keywords: 330